Investigation on the ski-snow interaction in a carved turn based on the actual measurement - Yoneyama, T.; Kitade, M.; Osada, K. (Procedia Engineering, 2010)
Based on the actual measurement on the ski deflection, ski-snow contacting pressure, boot-ski load, turn radius, snow groove geometry in a carved turn and the bending stiffness distribution of the ski, mutual relations have been investigated to elucidate the ski-snow interaction mechanism. Boot-ski load and the contacting pressure distribution on the running surface satisfy force equilibrium and moment equilibrium. The deflection of the ski is related with the moment distribution and bending stiffness distribution of the ski. The pattern of the pressure distribution changed with the bending stiffness distribution of the ski on the same hardness of the snow in the measurement.